Relationship between relative fat mass and low-carbohydrate diet scores and sleep disorders in United States: a real-world cross-sectional study - Cao, Cheng; Yu, Keyi; Lin, Fuquan; Xu, Aie; Zhou, Miaoni (Frontiers in Nutrition, 2024)
Objective: To investigate the relationship between relative fat mass (RFM) and low-carbohydrate diet (LCD) scores and sleep disorders in the U.S. population. Methods: Data were collected from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2014. A total of 5394 respondents participated in the study. Univariate and multivariate linear regression analyses were used to investigate the relationship between RFM and LCD scores, and univariate and multivariate logistic regression analyses were used to investigate the relationship between RFM and LCD scores and sleep disorders. Restricted cubic spline (RCS) analyses were conducted to test for nonlinear associations between RFM and LCD scores and sleep disorders. Results: A total of 5394 participants were included in the statistical analysis, including 5080 healthy participants and 314 with sleep disorders. Univariate and multivariate linear regression showed a bivariate positive correlation between RFM and LCD scores (P<0.05), and logistic regression analysis showed a significant positive correlation between RFM (95% CI: 1.02-1.07, P=0.005) LCD scores (95% CI: 1.00-1.03, P=0.044) and sleep disturbances. Subgroup analyses showed robust effects of RFM and LCD score on sleep disorders. Conclusion: RFM was positively and bi-directionally associated with LCD scores, both of which resulted as risk factors for sleep disorders. This study emphasizes that an LCD and lowering RFM can prevent and ameliorate the risk of sleep disorders.